Does Sound Influence Perceived Duration of Visual Motion? - Carlini, Alessandro; Bigand, Emmanuel (Frontiers in Psychology, 2021)
Multimodal perception is a key factor in obtaining a rich and meaningful representation of the world. However, how each stimulus combines to determine the overall percept remains a matter of research. The present work investigates the effect of sound on the bimodal perception of motion. A visual moving target was presented to the participants, associated with a concurrent sound, in a time reproduction task. Particular attention was paid to the structure of both the auditory and the visual stimuli. Four different laws of motion were tested for the visual motion, one of which is biological. Nine different sound profiles were tested, from an easier constant sound to more variable and complex pitch profiles, always presented synchronously with motion. Participants’ responses show that constant sounds produce the worst duration estimation performance, even worse than the silent condition; more complex sounds, instead, guarantee significantly better performance. The structure of the visual stimulus and that of the auditory stimulus appear to condition the performance independently. Biological motion provides the best performance, while the motion featured by a constant-velocity profile provides the worst performance. Results clearly show that a concurrent sound influences the unified perception of motion; the type and magnitude of the bias depends on the structure of the sound stimulus. Contrary to expectations, the best performance is not generated by the simplest stimuli, but rather by more complex stimuli that are richer in information.